An all-day solar-driven vapor generator via photothermal and Joule-heating effects. Issue 47 (20th November 2020) - Guo, Yang; Sui, Yujin; Zhang, Jiajie; Cai, Zaisheng; Xu, Bi
Abstract : An all-day operating solar evaporator is developed with the photothermal effect in combination with the Joule-heating effect. Abstract : To tackle global water pollution and shortage, solar-driven interfacial water evaporation has been demonstrated as a promising strategy for clean water generation. However, most of the previously reported interfacial evaporation systems only work in rich sunlight, which vastly limits their application under dark conditions. Herein, we propose an all-day solar-driven vapor generator based on metal foam via the photothermal effect in combination with Joule heating. A copper oxide (CuO) needle array and carbon black (CB) nanoparticles were assembled around a copper (Cu) skeleton to obtain CuO/Cu–CB foam with decent interfacial evaporation and salt resistance performance. The water evaporation rate reached 1.65 kg m −2 h −1 under one sun irradiation. Moreover, the vapor generation rate of the device reached 4.50 kg m −2 h −1 when a voltage as low as 2 V was applied. Besides, the CuO/Cu–CB foam can effectively remove the pollutants in the water and the methylene blue (MB) removal efficiency reached ∼98% without any oxide agents after 12 hours of illumination. Therefore, this all-day solar-driven vapor generation device supplies an effective pathway to mitigate freshwater scarcity.